2012
DOI: 10.1186/bcr3196
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between ER and NFκB in resistance to endocrine therapy

Abstract: Endocrine therapy is a commonly used treatment for estrogen receptor (ER)-positive breast cancer. Although endocrine therapy has a favorable outcome in many patients, development of resistance is common. Recent studies have shown that NFκB, a transcription factor regulating a wide variety of cellular processes, might play a role in the development of endocrine resistance. The precise interaction between ER and NFκB and how this contributes to the attenuated responsiveness of ER-positive breast cancer cells to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 77 publications
3
101
0
1
Order By: Relevance
“…These pathways have been shown to play a significant role in mammary carcinogenesis and have been implicated in tumor resistance. In particular, the NF-kB pathway has been shown to regulate cell proliferation, differentiation, and invasion (39). Similar to our study, the NF-kB pathway was reported to be increased by RRM2 and inhibited by didox, strengthening the findings that RRM2 is a key regulator of the NF-kB pathway (40,41).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These pathways have been shown to play a significant role in mammary carcinogenesis and have been implicated in tumor resistance. In particular, the NF-kB pathway has been shown to regulate cell proliferation, differentiation, and invasion (39). Similar to our study, the NF-kB pathway was reported to be increased by RRM2 and inhibited by didox, strengthening the findings that RRM2 is a key regulator of the NF-kB pathway (40,41).…”
Section: Discussionsupporting
confidence: 80%
“…Transrepression of ER by NF-kB has been proposed as a mechanism by which ER-positive breast tumor cells lose ER expression and, hence, gives rise to a subpopulation of tumor cells that are resistant to endocrine treatment (38,39). Furthermore, we provide evidence that increased NF-kB signaling leading to ERa alterations are mediated via RRM2 overexpression and can be reversed using didox through its ability to inhibit NF-kB activation (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…In this study, the levels of expression of several cytokines (including IL2, IL6, IL8, IFNg, CCL2, CCL4 and TNF) were inversely correlated with ER status and a subset (IL8, MCP1 and MIP1b) correlated with leukocyte infiltration (Chavey et al 2007). Inflammation has been shown to instigate and promote aggressive features in ER-positive breast cancer through the actions of cytokines on the interplay between ESR1 and NFkB, two key molecular switches within the breast tumour cell (recently reviewed by Baumgarten & Frasor (2012) and Sas et al (2012)). Activation of NFkB has been shown to cause acquired resistance and suppression of ESR1 in an MCF7 cell line model (Oida et al 2014), and downstream of NFkB signalling, the transcriptional repressor Blimp1 has been shown to suppress transcription of ESR1 by acting directly on the ESR1 promoter (Wang et al 2009).…”
Section: Mechanisms Of Inflammation-mediated Er Suppressionmentioning
confidence: 99%
“…Another prominent EMT-related transcription factor, Snail, has also been implicated in ER suppression and endocrine resistance (Dhasarathy et al 2007). Other internal cellular factors include acquired intracellular alterations in kinase signalling pathways (Brodie et al 2005, Massarweh et al 2006, Creighton et al 2010, Giamas et al 2011, trans-repression through upregulation of NFkB (Pradhan et al 2012, Sas et al 2012, effects of proteasome targeting factors (Man & Zhang 2011, Pan et al 2011 or microRNA expression (Guttilla et al 2012). Finally, suppression of ESR1 can also be caused by various extracellular factors including growth factors and cytokines (to be discussed below).…”
Section: Loss Of Esr1 In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation